THE INFLUENCE OF WORK DISCIPLINE AND SERVICE QUALITY ON CITIZEN SATISFACTION IN MEKAR JAYA VILLAGE, SEPATAN SUB-DISTRICT, TANGERANG DISTRICT - ariyanto, ariyanto (JURNAL ASIK, 2024)
The purpose of this study was to determine the influence of work discipline and service quality on citizen satisfaction in Mekar Jaya Village, Sepatan District, Tangerang Regency. The research method used in this research is descriptive with a quantitative approach. The population amounted to 1,652 people, this study used a sampling technique with the accidental sampling method and obtained a sample size in this study of 50 respondents. Data analysis techniques using multiple linear regression. The results showed that: (1) There is a positive and significant influence of work discipline variables on citizen satisfaction in Mekar Jaya Village, Sepatan District, Tangerang Regency. This is evidenced by the value of tcount> ttable, namely 5.834> 2.012 with a probability value (significance) = 0.000, which is below 0.005. (2) There is a positive and significant influence of service quality variables on citizen satisfaction in Mekar Jaya Village, Sepatan Subdistrict, Tangerang Regency. This is evidenced by the value of tcount> ttable, namely 6.108> 2.012 with a probability value (significance) = 0.000, which is below 0.005. (3) There is a positive and significant influence of work discipline and service quality variables on citizen satisfaction in Mekar Jaya Village, Sepatan Subdistrict, Tangerang Regency. This is evidenced by the value of Fcount> Ftable, namely 38.413> 3.20 with a probability value (significance) = 0.000, which is below 0.005.